Composite flocculant as well as preparation process and application thereof

By using amide flocculants, composite flocculants of polymeric aluminum chloride and water-soluble silicates, the problem of dust precipitation in high concentration waste sulfuric acid is solved, and effective dust precipitation and stability of the production system are achieved.

CN119240892AActive Publication Date: 2025-01-03安徽铜冠产业技术研究院有限责任公司 +1

Patent Information

Application Number
CN202411492809.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-03
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The prior art cannot effectively deal with the problem of dust in high concentrations of waste sulfuric acid, resulting in an increase in the area of ​​the precipitation tank and an extension of the precipitation time, affecting the stability of the production system.

Method used

Using a composite flocculant, including amide flocculant, polymer aluminum chloride and water-soluble silicate, a flocculant that can effectively precipitate dust under acidic conditions is formed through specific preparation processes and application steps.

Benefits of technology

The effective precipitation of dust in waste sulfuric acid is achieved, the area and precipitation time of the precipitation tank are reduced, and the stability of the production system is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a composite flocculant as well as a preparation process and application thereof, and relates to the technical field of waste acid treatment. Comprising 35%-55% wt of an amide flocculant (containing a strong anionic monomer containing a sulfonic acid group), a compound capable of generating high-valence metal ions and 0.2%-1.5% wt of water-soluble silicate. The composite flocculant disclosed by the invention not only contains hydrophilic groups such as sulfo groups and carboxyl groups with relatively strong polarity, but also contains a certain amount of metal ions with relatively high valence state, which is equivalent to crosslinking of the metal ions and amide polymers, so that the characteristic that polyacrylamide flocculants are difficult to hydrolyze under acidic or dilute acid conditions is mainly overcome; therefore, surface charges of suspended particles in a solution can be neutralized under an acidic or dilute acid condition, and destabilization of fine particles is realized. By using the composite flocculant, the dust in the waste sulfuric acid can generate a flocculation effect, the area of a waste sulfuric acid sedimentation tank is reduced, and the sedimentation time is shortened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waste acid treatment, and in particular to a composite flocculant, a composite flocculant preparation process and an application thereof. Background Art

[0002] At present, the washing circulating acid of the pyrite or smelting flue gas acid system mostly adopts the treatment devices such as sedimentation tanks, sedimentation tanks or filters. Due to the high concentration of waste sulfuric acid (sulfuric acid concentration is about 10% to 15% wt) and the temperature can reach 56°C, it is impossible to use conventional coagulants or flocculants to enhance precipitation.

[0003] Therefore, the dust content in the waste sulfuric acid after precipitation treatment is likely to exceed the production control requirements (150mg / L), sometimes up to 1g / L, resulting in production problems such as gas scrubber clogging and filter clogging. In order to alleviate this phenomenon, the only way is to increase the amount of waste acid treatment and flue gas washing supplementary water, which has the adverse effects of reducing the concentration of washing circulating acid (2% to 5%wt) and increasing the load of waste acid treatment.

[0004] Since the sulfuric acid concentration in the SO2 flue gas scrubbing circulating acid is about 2% to 15%wt, practice has shown that the existing commercially available flocculants, coagulants or coagulants cannot produce flocculation effect on the dust in the waste sulfuric acid. If the waste sulfuric acid treated by bypass precipitation is to be returned to the production system, the area of ​​the waste sulfuric acid precipitation tank can only be increased by nearly ten times and the precipitation time can be extended. Summary of the invention

[0005] In view of the above problems, the present invention provides a composite flocculant, a composite flocculant preparation process and an application. The invention is to solve the problem of high dust content in the recycling process of SO2 flue gas washing circulating acid, strengthen the dust precipitation (or sedimentation) in waste sulfuric acid, and improve the stability of the production system.

[0006] To solve the above problems, the technical solution adopted by the present invention is:

[0007] A composite flocculant comprises 35% to 55% by weight of an amide flocculant (containing a strong anionic monomer of a sulfonic acid group), a compound capable of generating high-valent metal ions and 0.2% to 1.5% by weight of a water-soluble silicate.

[0008] Preferably, the compound capable of generating high-valent metal ions is polyaluminium chloride, with a mass fraction of 2% to 10%wt.

[0009] A process for preparing a composite flocculant, for preparing the composite flocculant according to claim 1 or 2, comprising the following steps: S1, preparing an amide flocculant, a polyaluminium chloride solution and a water-soluble silicate; S2, first placing the amide flocculant in a production reaction stirring kettle, maintaining a predetermined reaction temperature while continuously stirring, then dripping the polyaluminium chloride solution, and after dripping for a predetermined time, when the solution pH is 3.5 to 4.5, ending the dripping of the polyaluminium chloride solution;

[0010] S3, after the addition of polyaluminium chloride is completed, a water-soluble silicate is added to the reactor. After a predetermined time, when the pH value of the solution is 4.8-5.2, the addition of the water-soluble silicate solution is terminated;

[0011] S4. Raise the operating temperature of the reactor, heat and concentrate the composite flocculant to obtain a finished composite flocculant (gel-like).

[0012] Preferably, the mass fraction of the polyaluminium chloride solution is about 13%, and the mass fraction of the water-soluble silicate is about 38%.

[0013] Preferably, in step S4, the operating temperature in the reactor is raised to 85-95° C., and the concentration of the amide flocculant in the output product is controlled to be 35%-55%wt.

[0014] Preferably, the production reaction stirred tank comprises a stirring device and a circulating pumping device, the stirring device is used to control the solutions at different horizontal positions to be fully mixed, and the circulating pumping device is used to control the solutions at different height positions to be fully mixed.

[0015] The invention discloses an application of a composite flocculant, wherein the composite flocculant is applied to waste acid to precipitate dust and particulate matter, and the application comprises the following steps: a first step, stirring and dissolving the prepared composite flocculant product with natural water to prepare a composite flocculant solution; a second step, extracting waste sulfuric acid of a certain concentration, wherein the concentration of sulfuric acid in the waste sulfuric acid is 2.63% to 8.95%; the concentration of dust (or suspended matter) is 12.86 g / L to 38.25 g / L; taking 400 mL of waste sulfuric acid and pouring it into a beaker, and stirring the waste sulfuric acid; a third step, adding a flocculant solution to be used into the waste sulfuric acid, wherein the flocculant solution is 2 mL to 12 mL, stirring for a predetermined time (5 s), adjusting the stirring speed to 50 rpm, stirring for about 10 min, then stopping the stirring, and standing for 2 h.

[0016] Preferably, the concentration of the flocculant solution in the first step is 0.25‰ to 0.5‰.

[0017] Preferably, the stirring speed in the second step is 350 rpm.

[0018] The beneficial effects of the present invention are:

[0019] Compared with the prior art, the composite flocculant of the present invention not only contains hydrophilic groups such as sulfonic acid groups and carboxyl groups with strong polarity, but also contains a certain amount of metal ions with higher valence, which is equivalent to the cross-linking of metal ions and amide polymers. It mainly overcomes the characteristic that polyacrylamide flocculants are difficult to hydrolyze under acidic or dilute acid conditions, thereby achieving the ability to neutralize the surface charge of suspended particles in the solution and destabilize fine particles under acidic or dilute acid conditions; the use of the above-mentioned composite flocculant can produce a flocculation effect on dust in waste sulfuric acid, reduce the area of ​​the waste sulfuric acid sedimentation tank, and shorten the sedimentation time. DETAILED DESCRIPTION

[0020] The present invention is further described below in conjunction with embodiments.

[0021] The furnace gas from the pyrite or smelting flue gas acid-making system (generally, the furnace gas temperature is controlled at dew point +20-30°C) enters the wet purification process and is first washed and dusted by circulating acid (sulfuric acid concentration ≯20%, also known as waste sulfuric acid), and the furnace gas temperature is reduced to below 60°C. The dust in the circulating acid gradually accumulates during the washing process.

[0022] In order to control the dust content of the circulating acid within the specified range (generally, it is required to be controlled below 30 mg / L), the circulating acid needs to be treated by bypass sedimentation. The clarified dilute sulfuric acid after treatment is returned to the production system, and the other part is transported to the waste acid treatment station for treatment. Whether the dilute sulfuric acid is returned to the production system or sent to the waste acid treatment station, the precipitation treatment of waste sulfuric acid can not only effectively recover dust, but also reduce the amount of solid waste generated.

[0023] At present, the washing circulating acid of the pyrite or smelting flue gas acid system mostly adopts the treatment devices such as sedimentation tanks, sedimentation tanks or filters. Due to the high concentration of waste sulfuric acid (sulfuric acid concentration is about 10% to 15% wt) and the temperature can reach 56°C, it is impossible to use conventional coagulants or flocculants to strengthen the precipitation. Therefore, the dust content in the waste sulfuric acid after precipitation treatment is easy to exceed the production control requirements (150mg / L), sometimes up to 1g / L, resulting in production problems such as clogging of the furnace gas washing tower and filter clogging. In order to alleviate this phenomenon, the only way is to increase the amount of waste acid treatment and the amount of flue gas washing supplementary water. The adverse effects are: reducing the concentration of the washing circulating acid (2% to 5% wt) and increasing the sharp increase in the waste acid treatment load.

[0024] Since the sulfuric acid concentration in the SO2 flue gas scrubbing circulating acid is about 2% to 15%wt, practice has shown that the existing commercially available flocculants, coagulants or coagulants cannot produce flocculation effect on the dust in the waste sulfuric acid. If the waste sulfuric acid treated by bypass precipitation is to be returned to the production system, the area of ​​the waste sulfuric acid precipitation tank can only be increased by nearly ten times and the precipitation time can be extended.

[0025] In order to solve the above problems, the present invention discloses a composite flocculant. The flocculant is prepared by an amide flocculant (containing a strong anionic monomer with a sulfonic acid group), polyaluminium chloride and a water-soluble silicate. The amide flocculant is synthesized by processes such as amidation, esterification and sulfonation of fatty acids, alcohol amine organic matter, acid anhydride, sulfonating agent and the like to obtain an amide flocculant containing polar groups such as sulfonic acid groups and carboxyl groups. The composite flocculant in the present invention is used to precipitate dust (or suspended matter) in waste sulfuric acid. According to the different concentrations of dust and sulfuric acid in the waste sulfuric acid to be treated, the preparation concentration and dosage of the composite flocculant are adjusted to achieve a better dust (or suspended matter) precipitation effect.

[0026] A composite flocculant is composed of 35% to 55% by weight of an amide flocculant (containing a strong anionic monomer with a sulfonic acid group), 2% to 10% by weight of polyaluminium chloride and 0.2% to 1.5% by weight of a water-soluble silicate.

[0027] The above-mentioned composite flocculant can reduce the dust content in waste sulfuric acid to 20 mg / L.

[0028] It should be noted here that the above-mentioned polyaluminium chloride can also be selected as other metal compounds that can produce high-valent metal ions and cross-link with amide polymers; technicians in this field can choose aluminium sulfate (Al2(SO4)3), iron sulfate (Fe2(SO4)3), etc. according to actual needs.

[0029] The composite flocculant of the present invention contains not only hydrophilic groups such as sulfonic acid groups and carboxyl groups with strong polarity, but also a certain amount of metal ions with high valence, which is equivalent to the cross-linking of metal ions and amide polymers. It mainly overcomes the characteristic that polyacrylamide flocculants are difficult to hydrolyze under acidic or dilute acid conditions, thereby achieving the ability to neutralize the surface charge of suspended particles in the solution and destabilize fine particles under acidic or dilute acid conditions.

[0030] The use of the above-mentioned composite flocculant can produce a flocculation effect on the dust in the waste sulfuric acid, reduce the area of ​​the waste sulfuric acid sedimentation tank, and shorten the sedimentation time.

[0031] When the composite flocculant solution is added to waste sulfuric acid, it undergoes multiple complex intermediate reactions. The entire reaction process can be roughly described by the monomer hydrolysis of the composite flocculant:

[0032]

[0033] Formula (1) can represent the hydrolysis product of the composite flocculant, which can neutralize the negative charge of dust in the waste sulfuric acid and adsorb and condense into larger particles. The anions close to the surface of the colloidal particles can be neutralized with the positive charge of the flocculant and become unstable. The introduction of silicate increases the sedimentation rate of the colloidal particles.

[0034] The dosage of the composite flocculant of the present invention is adjusted according to the concentrations of dust and sulfuric acid in the waste sulfuric acid to be treated, thereby achieving a better dust precipitation effect.

[0035] The following is a further explanation of the preparation process of the composite flocculant.

[0036] A composite flocculant preparation process, an amide flocculant preparation method is to use fatty acids, alcohol amine organic matter, acid anhydride, sulfonating agent, etc., according to the synthesis reaction steps, add fatty acids, alcohol amine organic matter, acid anhydride and sulfonating agent into a reaction container in sequence, add a proper amount of catalyst, and undergo amidation, esterification and sulfonation processes to synthesize an amide flocculant containing polar groups such as sulfonic acid group and carboxyl group.

[0037] In a production reaction stirring kettle, the concentration of the synthesized amide flocculant is controlled to be 20%-35%wt, the reaction temperature is maintained at 40-60°C, and the stirring speed is maintained at 30-75rpm, then a polyaluminium chloride solution with a mass fraction of about 13% is added dropwise, and the dropping time is controlled to be 90-120min. When the pH value of the solution is 3.5-4.5, the dropping of the polyaluminium chloride solution is terminated; after the dropping of the polyaluminium chloride is completed, a water-soluble silicate with a mass fraction of about 38% is added dropwise to the reactor, and the dropping time is controlled to be 30-60min. When the pH value of the solution is 4.8-5.2, the dropping of the water-soluble silicate solution is terminated; finally, the operating temperature of the reactor is increased to 85-95°C, the composite flocculant is heated and concentrated, and the concentration of the amide flocculant in the output is controlled to be 35%-55%wt, so that a finished composite flocculant (gel-like) is obtained.

[0038] In order to improve the effect of adding and mixing the polyaluminium chloride solution, the production reaction stirring kettle here includes a stirring device and a circulating pumping device. The stirring device can control the solution in the production reaction stirring kettle to rotate around the vertical axis, and control the solutions at different horizontal positions to be fully mixed.

[0039] The circulation pumping device includes a circulation pumping pipeline and a circulation pump. The circulation pumping pipeline is connected to the upper and lower ends of the production reaction stirring kettle, and can pump the solution at the bottom of the production reaction stirring kettle to the top for stirring and mixing. It can control the full mixing of solutions at different heights, greatly improve the overall solution mixing effect, improve the uniformity of solution preparation after dropwise addition, greatly shorten the dropwise addition stirring time, and improve the quality of the final finished composite flocculant.

[0040] The invention is further explained below in conjunction with the application of the composite flocculant.

[0041] The application of the composite flocculant to the waste acid to precipitate dust and particulate matter specifically includes the following steps.

[0042] The first step is to stir and dissolve the prepared composite flocculant product with natural water to prepare a composite flocculant solution, wherein the concentration of the flocculant solution is 0.25‰ to 0.5‰.

[0043] The second step is to extract a certain concentration of waste sulfuric acid, wherein the concentration of sulfuric acid in the waste sulfuric acid is 2.63% to 8.95%; the concentration of dust (or suspended matter) is 12.86 g / L to 38.25 g / L; 400 mL of waste sulfuric acid is poured into a beaker, and the waste sulfuric acid is stirred at a stirring speed of 350 rpm.

[0044] The third step is to add the flocculant solution to be used into the waste sulfuric acid, the flocculant solution is 2mL to 12mL, after stirring for a predetermined time (5s), adjust the stirring speed to 50rpm and stir for about 10min, then stop stirring and let it stand for 2h.

[0045] After standing, the supernatant was taken to determine the dust concentration, and the dust content in the waste sulfuric acid was measured to be reduced to 25 mg / L.

[0046] Example 1

[0047] Take 0.1 g of the prepared composite flocculant product (concentration of 50%), add 200 g of tap water and stir to dissolve, and use it as the flocculant solution (concentration of 0.5‰) to be used.

[0048] Take out the waste sulfuric acid sample from the production system for precipitation test. The sulfuric acid concentration of the waste sulfuric acid is 5.47% and the dust (or suspended matter) concentration is 12.86g / L. At room temperature (ambient temperature is about 30°C), take 400mL of waste sulfuric acid and pour it into a beaker, start stirring, stirring at a speed of 350rpm, add 2mL of the flocculant solution to be used to the waste sulfuric acid, stir for about 5s, then adjust the stirring speed to 50rpm and stir for about 10min, then stop stirring and let it stand for nearly 2h. The height of the mud layer is about 15% (measured by the height of the beaker), take the supernatant to measure the dust concentration, and the result is 22.5mg / L.

[0049] Example 2

[0050] Take 0.1 g of the prepared composite flocculant product (concentration of 50%), add 300 g of tap water and stir to dissolve, and use it as the flocculant solution to be used (concentration of about 0.3‰).

[0051] Take out the waste sulfuric acid sample from the production system for precipitation test. The sulfuric acid concentration of the waste sulfuric acid is 8.95% and the dust (or suspended matter) concentration is 38.25g / L. Take 400mL of waste sulfuric acid and pour it into a beaker. Start stirring in a water bath stirrer at a stirring speed of 350rpm. Add 10mL of the flocculant solution to be used into the waste sulfuric acid and stir for about 5s. Then adjust the stirring speed to 50rpm and stir for about 10min. Then stop stirring and let it stand for nearly 2h. The height of the mud layer is about 12% (measured by the height of the beaker). Take the supernatant to measure the dust concentration. The result is 27.8mg / L.

[0052] Example 3

[0053] Take 0.1 g of the prepared composite flocculant product (concentration of 50%), add 400 g of tap water and stir to dissolve, and use it as the flocculant solution (concentration of 0.25‰) to be used.

[0054] Take out the waste sulfuric acid sample from the production system for precipitation test. The sulfuric acid concentration of the waste sulfuric acid is 2.63% and the dust (or suspended matter) concentration is 15.72g / L. Take 400mL of waste sulfuric acid and pour it into a beaker. Start stirring in a water bath stirrer at a stirring speed of 350rpm. Add 12mL of the flocculant solution to be used into the waste sulfuric acid and stir for about 5s. Then adjust the stirring speed to 50rpm and stir for about 10min. Then stop stirring and let it stand for nearly 2h. The height of the mud layer is about 12% (measured by the height of the beaker). Take the supernatant to measure the dust concentration. The result is 17.5mg / L.

[0055] Comparative Example 1

[0056] The polyacrylamide used for waste acid neutralization treatment was used to test the waste acid precipitation dust, and the flocculant concentration was about 1.5‰.

[0057] Take out the waste sulfuric acid sample from the production system for precipitation test. The sulfuric acid concentration of the waste sulfuric acid is 3.68% and the dust (or suspended matter) concentration is 22.46g / L. Take 400mL of waste sulfuric acid and pour it into a beaker. Start stirring in a water bath agitator at a stirring speed of 350rpm. Add 12mL of the flocculant solution to be used to the waste sulfuric acid and stir for about 5s. Then adjust the stirring speed to 50rpm and stir for about 10min. Then stop stirring and let it stand for nearly 2h. The water-slag stratification phenomenon is not obvious, and the liquid on the top of the beaker is still maroon. Take the supernatant to measure the dust concentration. The result is 12.36g / L, which is difficult to meet the needs of production reuse.

[0058] Comparative Example 2

[0059] The polyacrylamide used for waste acid neutralization treatment was used to test the waste acid precipitation dust, and the flocculant concentration was about 4.5‰.

[0060] Take out the waste sulfuric acid sample from the production system for precipitation test. The sulfuric acid concentration of the waste sulfuric acid is 2.85% and the dust (or suspended matter) concentration is 10.15g / L. Take 400mL of waste sulfuric acid and pour it into a beaker. Start stirring in a water bath agitator at a stirring speed of 350rpm. Add 10mL of the flocculant solution to be used to the waste sulfuric acid and stir for about 5s. Then adjust the stirring speed to 50rpm and stir for about 10min. Then stop stirring and let it stand for nearly 2h. The water-slag stratification phenomenon is not obvious, and the liquid on the top of the beaker is still light red. Take the supernatant to measure the dust concentration. The result is 0.98g / L, which is difficult to meet the needs of production reuse.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite flocculant, characterized in that: The invention comprises 35% to 55% by weight of an amide flocculant, wherein the amide flocculant contains a strong anionic monomer of a sulfonic acid group, and further comprises a compound capable of generating high-valent metal ions and 0.2% to 1.5% by weight of a water-soluble silicate.

2. The composite flocculant according to claim 1, characterized in that: The compound capable of generating high-valent metal ions is polyaluminium chloride, with a mass fraction of 2% to 10%wt.

3. A process for preparing a composite flocculant, characterized in that: The method for preparing the composite flocculant according to claim 1 or 2 comprises the following steps: S1. preparing an amide flocculant, a polyaluminium chloride solution and a water-soluble silicate; S2, first placing an amide flocculant in a production reaction stirring tank, maintaining a predetermined reaction temperature while continuously stirring, then dripping a polyaluminium chloride solution, and after a predetermined time of dripping, when the solution pH = 3.5-4.5, ending the dripping of the polyaluminium chloride solution; S3, after the addition of polyaluminium chloride is completed, a water-soluble silicate is added to the reactor. After a predetermined time, when the pH value of the solution is 4.8-5.2, the addition of the water-soluble silicate solution is terminated; S4. Raise the operating temperature of the reactor, heat and concentrate the composite flocculant to obtain a finished product of the gel-like composite flocculant.

4. The preparation process of the composite flocculant according to claim 3, characterized in that: The mass fraction of the polyaluminium chloride solution is about 13%, and the mass fraction of the water-soluble silicate is about 38%.

5. The preparation process of the composite flocculant according to claim 3, characterized in that: In step S4, the operating temperature in the reactor is raised to 85-95° C., and the concentration of the amide flocculant in the output product is controlled to be 35%-55%wt.

6. The preparation process of the composite flocculant according to claim 3, characterized in that: The production reaction stirred tank comprises a stirring device and a circulating pumping device. The stirring device is used to control the solutions at different horizontal positions to be fully mixed, and the circulating pumping device is used to control the solutions at different height positions to be fully mixed.

7. An application of a composite flocculant, characterized in that: Applying the composite flocculant according to claim 1 or 2 to precipitate dust and particulate matter in waste acid comprises the following steps: The first step is to stir and dissolve the prepared composite flocculant product with natural water to prepare a composite flocculant solution; The second step is to extract a certain concentration of waste sulfuric acid, wherein the concentration of sulfuric acid in the waste sulfuric acid is 2.63% to 8.95%; the concentration of dust or suspended matter is 12.86 g / L to 38.25 g / L; 400 mL of waste sulfuric acid is poured into a beaker and the waste sulfuric acid is stirred; The third step is to add the flocculant solution to be used into the waste sulfuric acid, the flocculant solution is 2mL to 12mL, after stirring for a predetermined time, adjust the stirring speed to 50rpm and stir for about 10min, then stop stirring and let it stand for 2h.

8. The use of the composite flocculant according to claim 7, characterized in that: The concentration of the flocculant solution in the first step is 0.25‰ to 0.5‰.

9. The use of the composite flocculant according to claim 7, characterized in that: The stirring speed in the second step was 350 rpm.

Citation Information

Patent Citations

  • Composite flocculant, preparation method thereof and livestock and poultry biogas slurry pretreatment method

    CN111115780A

  • Shale gas well drilling waste oil-based mud curing material

    CN112794590A

  • Method and system for treating suspended matters in desulfurization wastewater

    CN113200622A

  • Inorganic composite flocculant as well as preparation method and application thereof

    CN115838205A

  • Preparation method of basic aluminum sulfate coagulant using waste sulfuric acid, basic aluminum sulfate inorganic coagulant prepared by the above method and water treatment method using the same

    KR102702043B1

Cited By

  • Stirring tank for polyferric sulfate production and control method thereof

    CN120523268A